The resonance of moderate feminism and the gendered relations of austerity. Issue 8 (20th November 2018) - Budgeon, Shelley
Abstract : During the tenure of the UK Conservative‐led coalition government (2010–15) austerity policy was rolled out in response to the global financial crisis of 2007–08. In this article a discourse analysis of mainstream newspaper representations of austerity, which appeared throughout this period, is undertaken using the principles of Cultural Political Economy (Jessop 2004). Three key questions are posed: 1) How is gender drawn upon to render austerity intelligible? 2) How do these discursive constructions contribute to the reproduction of particular ideas regarding contemporary gender relations? 3) What do these gendered austerity discourses reveal about the institutionalisation of particular forms of feminism? A critical gender discourse which emphasised equality appeared alongside constructions of gender that reproduced problematic assumptions. Made meaningful in this way, austerity, as a strategy for restoring pre‐crash social arrangements, also restored particular aspects of gender relations. This is theorised as the product of the successful institutionalisation of a hegemonic, moderate liberal feminism prior to the financial crash. The findings contribute to debates within feminist scholarship about the dynamics of gender inclusion and extend our understanding of the associated implications for feminist critique.